Biochemical and structural analysis of the molybdenum cofactor biosynthesis protein MobA - Guse, Annika (The journal of biological chemistry, 2003)
Molybdopterin guanine dinucleotide (MGD) is the form of the molybdenum cofactor that is required for the activity of most bacterial molybdoenzymes. MGD is synthesized from molybdopterin (MPT) and GTP in a reaction catalyzed by the MobA protein. Here we report that wild type MobA can be copurified along with bound MPT and MGD, demonstrating a tight binding of both its substrate and product. To study structure-function relationships, we have constructed a number of site-specific mutations of the most highly conserved amino acid residues of the MobA protein family. Variant MobA proteins were characterized for their ability to support the synthesis of active molybdenum enzymes, to bind MPT and MGD, to interact with the molybdenum cofactor biosynthesis proteins MobB and MoeA. They were also characterized by x-ray structural analysis. Our results suggest an essential role for glycine 15 of MobA, either for GTP binding and/or catalysis, and an involvement of glycine 82 in the stabilization of the product-bound form of the enzyme. Surprisingly, the individual and double substitution of asparagines 180 and 182 to aspartate did not affect MPT binding, catalysis, and product stabilization.